An extremely low Pt loading cathode for a highly efficient proton exchange membrane water electrolyzer - Kim, Hoyoung; Choe, Seunghoe; Park, Hyanjoo; Jang, Jong Hyun; Ahn, Sang Hyun; Kim, Soo-Kil (ROYAL SOC CHEMISTRY, 2017)
Direct self-terminated Pt electrodeposition on carbon paper enables precise control of loading Pt mass, from the sub-microgram to the sub-milligram scale. This can provide insight into the low limits of Pt use for reasonable performance of a proton exchange membrane water electrolyzer.